Answer:
9(9 + x) = -25
x = 6.22222 repeating
Explanation:
First, we have to distribute. 9 times 9 = 81 and 9 times x = 9x. The equation now becomes 81 + 9x = -25.
Second, we have to get the coefficient alone. Since the opposite of positive 81 is negative 81, we subtract it to get 0. Since we did that to one side we have to do it to the other. -25 - (-81) = 56. Now we have 9x = 56.
Third, we have to get the variable by itself. To do that we divide 9 by 9 to get 0 and that gets the variable alone. Since we did that to one side we have to do it to the other. 56 divided by 9 = 6.222 with the 2 repeating over 8 times.